Gender Differences in Coronary Artery Diameter Are Not Related to Body Habitus or Left Ventricular Mass. Issue 10 (30th September 2014) - Hiteshi, Amit K.; Li, Dong; Gao, Yanlin; Chen, Andy; Flores, Ferdinand; Mao, Song Shou; Budoff, Matthew J.
Abstract Background Smaller coronary artery diameter portends worse outcomes after coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI). The suggestion that women have smaller coronary artery diameters than men has not been validated by a large‐scale study. Hypothesis We sought to confirm a gender difference with respect to coronary artery diameter, even after accounting for body habitus and left ventricular mass (LVM). Methods From 4200 subjects evaluated for cardiovascular disease by computed tomography angiography, we selected 710 subjects (383 males, 327 females) with coronary artery calcium (CAC) scores <100, eliminating patients with artery remodeling. Diameters of the left main (LM), left anterior descending (LAD), left circumflex (CX), and right coronary arteries (RCA), were measured. Measurements were compared using a 2‐sample t test and the multiple regression model, accounting for body habitus and LVM. Results After adjusting for age, race, weight, height, body mass index, body surface index, LVM, and CAC, women have smaller diameters in the LM (males 4.35 mm, females 3.91 mm), LAD (males 3.54 mm, females 3.24 mm), CX (males 3.18, females 2.75 mm), and RCA (males 3.70 mm, females 3.26 mm) (P < 0.001). This difference is not related to body habitus or LVM. Conclusions Gender significantly influences artery diameter of the LM, LAD, CX, and RCA. This may warrant gender specific approaches during PCI and CABG. As neither body habitus nor LVM relate to the difference in coronary artery diameter, our study encourages a search for inherent differences between genders that can account for this difference.